Worldwide Status of Fresh Fruits Irradiation and Concerns about Quality, Safety, and Consumer Acceptance. Issue 11 (17th August 2016) - Shahbaz, Hafiz Muhammad; Akram, Kashif; Ahn, Jae-Jun; Kwon, Joong-Ho
ABSTRACT: Development of knowledge-based food preservation techniques have been a major focus of researchers in providing safe and nutritious food. Food irradiation is one of the most thoroughly investigated food preservation techniques, which has been shown to be effective and safe through extensive research. This process involves exposing food to ionizing radiations in order to destroy microorganisms or insects that might be present on and/or in the food. In addition, the effects of irradiation on the enzymatic activity and improvement of functional properties in food have also been well established. In the present review, the potential of food irradiation technology to address major problems, such as short shelf life, high-initial microbial loads, insect pest management (quarantine treatment) in supply chain, and safe consumption of fresh fruits was described. With improved hygienic quality, other uses, such as delayed ripening and enhanced physical appearance by irradiation were also discussed. Available data showed that the irradiation of fruits at the optimum dose can be a safe and cost-effective method, resulting in enhanced shelf life and hygienic quality with the least amount of compromise on the various nutritional attributes, whereas the consumer acceptance of irradiated fruits is a matter of providing the proper scientific information.